COMPARISON OF OXIDATIVE STRESS PARAMETERS BETWEEN DIABETIC AND OBESE PATIENTS - KAVEH BAHRAMI,; ZAHRA ASHKAVAND, (International Journal of Pharma and Bio Sciences, 2014)
Oxidative stress and inflammation are implicated in the initiation and development of obesity and diabetes .This study investigated the comparison of important oxidative stress parameters between diabetic and obese patients and it is significantly (p < 0.05) showed that the level of oxidative stress is more in obese. Level of Hs-CRP also has been increased in the obese patients. It is revealed that oxidative stress has a main role in this disease.